Occurrences related to the use of central and peripheral intravenous devices periféricos - Joao Luiz Grandi, Mariana Cabrera Grell, Dulce Aparecida Barbosa (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/2238-7234.724-10